Ultrasensitive electrochemical detection of Dicer1 3′UTR for the fast analysis of alternative cleavage and polyadenylation. Issue 12 (15th March 2017) - Zhao, Hui; Liu, Feng; Wu, Shilian; Yang, Long; Zhang, Ya-Ping; Li, Can-Peng
Abstract : A schematic diagram for the stepwise assembly procedure of the electrochemical sensor and its analysis of APA. Green line represents the capture probes to hybridize the 3′UTR of Dicer1 gene. CP: capture probe; AP: auxiliary probe; LP: label probe. Abstract : Alternative cleavage and polyadenylation (APA) is involved in several important biological processes in animals, e.g. cell growth and development, and cancer progression. The increasing data show that cancer cells are inclined to produce mRNA isoforms with a shortened 3′UTR undergoing APA. For example, the Dicer1 isoform with a shorter 3′untranslated region (3′UTR) was found to be overexpressed in some cancer cells, which may be used as a potential novel prognostic biomarker for cancer. In the present work, a novel electrochemical biosensor for ultrasensitive determination of Dicer1 was designed by using gold nanoparticles and p -sulfonated calix[6]arene functionalized reduced graphene oxide (Au@SCX6-rGO) as nanocarriers. The results showed that the expressions of the shorter 3′UTR ( Dicer1 -S) both in BT474 and SKBR3 were obviously higher than those of the longer Dicer1 ( Dicer1 -L) by the constructed biosensor, which agreed well with the result analyzed by the RT-qPCR method. The detection ranges of Dicer1 -S and Dicer1 -L were 10 −14 –10 −9 M and 10 −15 –10 −10 M. The LODs were 3.5 and 0.53 fM. The specificity of the proposed biosensor was also very high. For the first time, the expressional analysis of different 3′UTRs caused by APA was studied by an electrochemical method. Moreover, the use of a macrocyclic host for constructing an electrochemical/biosensing platform has rarely been reported. The proposed electrochemical sensing strategy is thus expected to provide a new method for determination of novel biomarkers and a novel method for fast and cheap analysis of APA.